FORMULATION AND EVALUATION OF MELOXICAM LOADED NANOEMULGEL FOR TOPICAL DRUG DELIVERY - Raj R, Arun (Innoriginal: International Journal of Sciences, 2019)
Objective: To formulate and evaluate meloxicam loaded nanoemulgel for topical drug delivery. Methods: Nanoemulsion is prepared by spontaneous emulsification technique.Â  Nanoemulgel is prepared by adding nanoemulsion in to the gel matrix. Characterization of meloxicam loaded nanoemulgel were performed. Results: The nanoemulgel was evaluated for clarity, homogenicity, pH, viscosity, percentage drug entrapment and In vitro drug release study. The results of the formulation was found to be satisfactory. The drug content was within acceptable range. The drug release mechanism from the tablets was found to be non fickian transport kind of diffusion. Conclusion: Meloxicam nanoemulgel can be effectively used for topical drug delivery. Keywords: Meloxicam, Nanoemulsion, Nanoemulgel, spontaneous emulsification.